Multifunctional oxide heterostructures - Tsymbal, E. Y. (Evgeny Y.) (Oxford : Oxford University Press, 2012)
This volume explores the rapidly developing field of oxide thin-films and heterostructures, which exhibit unusual physical properties interesting from the fundamental point of view and for device application. The chapters discuss topics that represent some of the key innovations in the field over recent years.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Oxides; Thin films; Heterostructures